Preferensi Pemilihan Moda Transportasi Menggunakan Kereta Api, Travel, dan Mobil Pribadi (Studi Kasus: Rute Bandar Lampung – Palembang) - Anggraeni, Salmani Syindi; Sulistyorini, Rahayu; Karami, Muhammad (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2024)
Passenger characteristics greatly affect passengers in choosing the mode of transportation. This study aims to determine the factors that influence travelers and the utility equation model of mode selection between trains, travel, private cars. This research was conducted by distributing questionnaires to the people of Bandar Lampung city. The method used is the Stated Preference model. The research resulted in characteristic factors that significantly influence the selection of transportation modes, namely X1 = income, X2 = cost, X3 = travel time. The following is the value of the Utility equation: Y Railway = 0.2398 x1 - 0.2847 x2 + 0.2924 x3 + 0.0237, R2 Railway = 0.7131. YTravel = 0.1548 x1 + 0.1605 x2 + 0.0714 x3 - 0.3824, R2Travel = 0.3520. YPrivate Car = 0.2395 x1 - 0.2845 x2 + 0.2924 x3 - 0.0241, R2Private Car = 0.7128.